Aplikasi Beads Komposit Chitosan – Clay Sebagai Adsorben dalam Penyerapan Ion Klorida (Cl-) Pada Air Payau: Application of Chitosan – Clay Composite Beads as Adsorbent to Removal of Cl- Ions in Brackish - Syavina Ananda; Shinta Elystia; Dewi Fitria (LPPM Universitas Mataram, 2023)
Water resources found in coastal areas and islands in terms of water quality are still relatively low, so treatment is necessary. Chitosan and clay are adsorbents that can be applied in various techniques to overcome environmental pollution. Chitosan is a natural adsorbent that has a high adsorption capacity but has low mechanical stability and is easily dissolved in an acidic medium. Clay is an adsorbent with a large specific surface area and has high mechanical stability. This research uses chitosan – clay beads, which aim to increase mechanical stability environmental resistance, and efficiency in brackish water treatment. It is located in Bandar Sungai Village, Sabak Auh District, Siak Regency. The research was conducted by varying the concentration of chitosan–clay beads (1:0), (1:0,25), (1:0,5), and (1:0,75) (w/w) to decrease the chloride ion (Cl-) in brackish water. The characterization of chitosan-clay beads with the water absorption test obtained the best results at the concentration variation (1:0), which was equal to 694,079%. The mechanical strength test obtained the best results at the concentration variation (1:0,75), which was 6,23 kgf. The characterization of chitosan-clay beads using SEM showed that the beads had larger pores. The results obtained show the best chloride ion removal efficiency (Cl-) of 90,828% with a final concentration of 113 mg/L at a concentration of chitosan – clay beads of (1:0.5) with a sampling time of 30 minutes. The research results have met the quality standards set by the Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management.